Effects of Religious Discrimination and Fear for Safety on Life Satisfaction for Muslim Americans - Kimberly Langrehr; Ramy Bassioni (Journal of Muslim Mental Health)
Objectives: The purpose of the current study was to examine the relationship between two forms of religious discrimination (religious prejudice and environmental discrimination) and life satisfaction among a sample of Muslim Americans. Based on the framework of minority stress theory, we also hypothesized that higher levels of religious prejudice as well as environmental discrimination, would significantly relate to higher fear of safety, and in turn, would relate to lower life satisfaction. Method: A total of 192 Muslim American participants (Age M= 27.87) completed an on-line survey about their experiences as Muslim American. Women made up almost 75% of the sample.Results: Findings revealed that higher religious prejudice as well as environmental discrimination were both significantly related to lower life satisfaction and that fear of safety partially mediated both of these relationships. Conclusions:  Findings help illustrate that Muslim Americans are not immune to the social-political climate of Islamophobia and can experience religious discrimination in different ways. In addition, women and younger participants expressed higher fear of safety when compared to men and older participants. Professionals who work with individuals from the Muslim community are encouraged to consider the chronic and on-going impact of stress that Muslim Americans face especially within the context of the United States.